Putting Embedded Ethics and Social Science into practice: the role of peer-to-peer relationships - Svenja Breuer; Sophia Witz; Jon Skerlj; Maximilian Braun; Marieke Bak; Abdeldjallil Naceri; Daniel Tigard; Sami Haddadin; Alena Buyx; Iris Eisenberger; Ruth Müller (Journal of Responsible Innovation)
In response to the ethical and societal challenges of emerging technologies, there is a growing commitment to integrative socio-technical research. One such approach is embedded ethics and social science, which embeds the analysis of ethical, social, and legal aspects into the entire innovation process through direct collaboration between ethicists, social scientists, legal scholars, technical researchers, and experts in the field of application. We offer reflections on our experiences from the approach's pilot project, Responsible Robotics, where we were integrated into a research project on service robotics for senior care. Drawing on more than four years of embedded research, we present practices through which peer-to-peer relationships develop. These relationships challenge disciplinary identities and serve as grounds for mutual learning and capacity-building. Our insights contribute to the discourse on how science and technology studies (STS), ethics, and law can integrate with technological research to ensure ethically and socially responsible practices.